Problem-solving method with semantic net based on DNA computing in artificial intelligence - Tsuboi, Yusei; Ibrahim, Zuwairie; Ono, Osamu (IEEE, 2004)
Semantic Net is among the problem solving systems in artificial intelligence fields. In this paper, we demonstrate how to design DNA-typed Semantic Net in order to apply DNA computing to artificial intelligence. Moreover, we propose a problem-solving method with DNA-typed Semantic Net. In this method, it is possible to reason out a reference object by using DNA computing algorithm. Proposed DNA-typed Semantic Net is used as a molecular knowledge based system. Vertexes and edges of the DNA-typed Semantic Net are encoded to four kinds of nucleotide. Single-stranded DNAs are hybridized and ligated to let them the double-stranded DNAs with the complementary sequences of input molecules and knowledge based ones. For the molecular knowledge based system, we estimate the computational complexity by using a simulation. Proposed problem-solving method is performed by DNA-based computer for a future generation of artificial intelligence.